The orphan receptor TR3 suppresses intestinal tumorigenesis in mice by downregulating Wnt signalling. Issue 5 (28th August 2011) - Chen, Hang-Zi; Liu, Qing-Feng; Li, Li; Wang, Wei-Jia; Yao, Lu-Ming; Yang, Meng; Liu, Bo; Chen, Wei; Zhan, Yan-Yan; Zhang, Ming-Qing; Cai, Jian-Chun; Zheng, Zhong-hui; et al.
Abstract : Aims: Wnt signalling is involved in cellular homeostasis and development. Dysregulation of the Wnt signalling pathway has been linked to colorectal cancer. The orphan nuclear receptor TR3 plays important roles in proliferation and apoptosis. In this study, we investigated how TR3 suppresses intestinal tumorigenesis by regulating Wnt signalling. Methods: Intestinal polyps were quantified in Apc min/+, Apc min/+ /TR3 −/− and Apc min/+ /villin-TR3 mice. Wnt signalling activity was evaluated by assessing β-galactosidase activity in a BAT-Gal reporter strain. The TR3 agonist cytosporone B was used to evaluate the role of TR3 in intestinal tumorigenesis. Crosstalk between TR3 and β-catenin/TCF4 was analysed by molecular methods in colorectal cancer cells. The phosphorylation of TR3 by glycogen synthase kinase (GSK) 3β and the correlation between GSK3β activity and TR3 phosphorylation were evaluated in clinical samples and colorectal cancer cells. Results: TR3 was found to significantly suppress Wnt signalling activity and the proliferation of intestinal epithelial cells. Apc min/+ /TR3 −/− mice developed more intestinal polyps than Apc min/+ /TR3 +/+ mice, whereas either transgenic overexpression of TR3 in the intestine or treatment with cytosporone B in Apc min/+ mice significantly decreased intestinal tumour number. Mechanistically, TR3 disrupted the association of β-catenin and TCF4 on chromatin and facilitated the recruitment of transcriptional co-repressors to the promoters of Wnt signalling target genes. However, TR3 was phosphorylated by GSK3β in most clinical colorectal cancers, which attenuated the inhibitory activity of TR3 towards Wnt signalling. Conclusions: TR3 is a negative regulator of Wnt signalling and thus significantly suppresses intestinal tumorigenesis in Apc min/+ mice. This inhibitory effect of TR3 may be paradoxically overcome through phosphorylation by GSK3β in clinical colorectal cancers.